Pre-Competition Anxiety and Self-Confidence of Wheelchair Basketball Players from China, Taiwan and Hong Kong. - Yang, Jinjin (2005)
Keywords: dept.hms; faculty_collection

The Lives and Travels of Mormon & Moroni - Ainsworth, Jerry L. (Peacemakers Pub., 2000)
Keywords: Biography; Mormon (Book of Mormon figure); Moroni (Book of Mormon figure); Book of Mormon; dept.hms; faculty_collection

Exercise modifications and strategies to enhance shoulder function - Ronai, P. (Strength and Conditioning Journal, 2005)
The purposes of this article are to identify exercise performance-related factors that may contribute to shoulder pain and dysfunction and to describe appropriate training strategies for promoting shoulder stability and enhanced function. This article is not intended to help the reader diagnose and treat injuries or prescribe therapeutic interventions. Strength and conditioning professionals should encourage injured clients to consult a physician, physical therapist, or other appropriate health care professional before starting a conditioning program. © National Strength and Conditioning Association.
8 citations (Crossref) [2023-10-31]
Keywords: Exercise technique; Flexibility; Posture; Rotator cuff impingement; Scapular stability; Sensorimotor control; Strength; dept.hms

Resistance training for persons with osteoarthritis and rheumatoid arthritis - Ronai, P.; Sorace, P.; LaFontaine, T. (Strength and Conditioning Journal, 2008)
Arthritic conditions affect more than 40 million americans and are a major cause of physical disability. Resistance training has been found to improve muscular performance in persons with osteoarthritis and rheumatoid arthritis. This column discusses the benefits of resistance training in persons with osteoarthritis and rheumatoid arthritis and provides general suggestions for developing safe, effective resistance training programs. © National Strength and Conditioning Association.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms

The effects of a 10-week, periodized, off-season resistance-training program and creatine supplementation among collegiate football players. - Wilder, Nathan; Gilders, Roger; Hagerman, Frederick; Deivert, Richard G (Journal of strength and conditioning research, 2002)
The periodized resistance-training model has not been well documented in the literature. Further research is needed to determine if periodized resistance training in conjunction with creatine supplementation can cause changes in strength, performance, total body weight, girth, and lean muscle mass. Therefore, the purpose of this investigation was to determine the effects of periodized resistance training in conjunction with low-dose (LD) and high-dose (HD) creatine supplementation on strength, body composition, and anaerobic muscular endurance. Subjects were divided into 3 groups: LD, HD, and placebo (P). Testing took place pre-, mid-, and postsupplementation for the following: weight, body composition (fat-free mass and fat mass), 1 repetition maximum squat, and anaerobic muscular endurance testing. Results revealed no significant differences in either creatine group when compared with the P group. However, significant differences were noted over time. These data suggest that 10 weeks of periodized resistance training was effective for causing changes in strength, body composition, and anaerobic muscular endurance.
1 citations (Crossref) [2023-10-31] Place: United States Wilder, Nathan. Southern Connecticut State University, New Haven 06515, USA. wilder@southernct.edu
Keywords: *Creatine/ad [Administration & Dosage]; *Dietary Supplements; *Exercise/ph [Physiology]; *Football; Adolescent; Adult; Anaerobiosis; Anthropometry; Body Composition; Body Weight; Creatine; Dietary Supplements; Exercise; Football; Humans; Male; Muscle; Skeletal; Muscle; Skeletal/ph [Physiology]; Periodization; Physical Endurance; Resistance training; Single-Blind Method; Supplementation; adolescence; adult; anaerobic growth; anthropometry; article; athlete; body composition; body weight; controlled study; creatine; dept.hms; diet supplementation; exercise; football; human; male; muscle exercise; muscle mass; muscle strength; normal human; peer-reviewed; performance; physical stress; physiology; single blind procedure; skeletal muscle; supplementation; training; ❓ Multiple DOI

Effects of sprint interval training and body weight reduction on power to weight ratio in experienced cyclists. - Lunn, William R; Finn, Joan A; Axtell, Robert S (Journal of strength and conditioning research, 2009)
The purpose of this study was to determine the effect of supramaximal sprint interval training (SIT), body weight reduction, and a combination of both treatments on peak and average anaerobic power to weight ratio (PPOan:Wt, APOan:Wt) by manipulating peak and average anaerobic power output (PPOan, APOan) and body weight (BW) in experienced cyclists. Participants (N = 34, age = 38.0 +/- 7.1 years) were assigned to 4 groups for a 10-week study. One group performed twice-weekly SIT sessions on a cycle ergometer while maintaining body weight (SIT). A second group did not perform SIT but intentionally reduced body weight (WR). A third group simultaneously performed SIT sessions and reduced body weight (SIT+WR). A control group cycled in their normal routine and maintained body weight (CON). The 30-second Wingate Test assessed pretest and posttest POan:Wt scores. There was a significant mean increase (p < 0.05) from pretest to posttest in PPOan:Wt and APOan:Wt (W x kg(-1)) scores in both SIT (10.82 +/- 1.71 to 11.92 +/- 1.77 and 8.05 +/- 0.64 to 8.77 +/- 0.64, respectively) and WR (10.33 +/- 2.91 to 11.29 +/- 2.80 and 7.04 +/- 1.45 to 7.62 +/- 1.24, respectively). PPOan and APOan (W) increased significantly only in SIT (753.7 +/- 121.0 to 834.3 +/- 150.1 and 561.3 +/- 62.5 to 612.7 +/- 69.0, respectively). Body weight (kg) decreased significantly in WR and SIT + WR (80.3 +/- 13.7 to 75.3 +/- 11.9 and 78.9 +/- 10.8 to 73.4 +/- 10.8, respectively). The results demonstrate that cyclists can use SIT sessions and body weight reduction as singular training interventions to effect significant increases in anaerobic power to weight ratio, which has been correlated to enhanced aerobic cycling performance. However, the treatments were not effective as combined interventions, as there was no significant change in either PPOan:Wt or APOan:Wt in SIT + WR.
7 citations (Crossref) [2023-10-31] Place: United States Lunn, William R. Exercise Science Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. wlunn25@comcast.net
Keywords: *Bicycling/ph [Physiology]; *Physical Education and Training/mt [Methods]; *Weight Loss; Adult; Analysis of Variance; Bicycling; Body Composition; Body Mass Index; Body Weight; Female; Humans; Male; Physical Education and Training; Physical Endurance; Physical Endurance/ph [Physiology]; Reproducibility of Results; Weight Loss; Wingate test; adult; analysis of variance; article; bicycle; body composition; body mass; body weight; dept.hms; endurance; female; human; male; methodology; peer-reviewed; physical education; physiology; reproducibility; weight reduction

The performance-level model of hospital decontamination preparedness. - Phelps, Scot; Doering, Garrett (American journal of disaster medicine, 2008)
OBJECTIVE: Describe a multilevel model of decontamination capacity for hospitals., DESIGN: Descriptive model., SETTING: Acute care hospitals with decontamination responsibilities., PATIENTS, PARTICIPANTS: None., INTERVENTIONS: None., MAIN OUTCOME MEASURE(S): None., RESULTS: This multilevel model of defining decontamination capacity would allow more realistic assessment of current capacity, allow for fluctuating service levels depending on time of day, incorporate realistic ramp-up and ramp-down of decontamination services, allow for a defined fall-back decontamination model should decontamination processes fail, allow hospitals to define long-term decontamination service level goals, and allow better understanding of when and why to focus on low-risk/low-resource patients rather than high-risk/high-resource patients., CONCLUSIONS: This multiple-level model would allow for more realistic and effective hospital-based decontamination service models and should become part of the national decontamination paradigm.
1 citations (Crossref) [2023-10-31] Place: United States Phelps, Scot. Department of Public Health, School of Health and Human Services, Southern Connecticut State University, New Haven, USA.
Keywords: *Decontamination/st [Standards]; *Disaster Planning/st [Standards]; *Emergency Service; Hospital/og [Organization & Administration]; *Hospital Administration/st [Standards]; *Models; Organizational; Decontamination; Disaster Planning; Emergency Service; Hospital; Hospital Administration; Hospitals; Hospitals/st [Standards]; Humans; MLCS; MLOWN; Models; Organizational; Terrorism; article; dept.hms; disaster planning; emergency health service; hospital; hospital management; human; nonbiological model; organization and management; standard; terrorism; waste management

Managing ball retrieval in skill practice situations - Webb, Daniel; Kozub, Francis M; Yang, Jinjin (Strategies, 2003)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-980-621-552-82X
Keywords: dept.hms

A focus group study of DES daughters: implications for health care providers. - Duke, Suzanne S; Mcgraw, Sarah A; Avis, Nancy E; Sherman, Amanda (Psycho-oncology, 2000)
A focus group study of women exposed to diethylstiibestrol (DES) in utero (DES daughters) was conducted to gain understanding about exposure to this drug from a patient perspective. Focus group participants reported that learning about their DES exposure was devastating; they experienced strains in their family relationships, emotional shock, a feeling that their health concerns were not appreciated by others and, to some degree, a sense of social isolation. Although many were aware of the need for special gynecological exams and high-risk prenatal care, they were frustrated by what they felt was a lack of reliable and clear information about the effects of DES exposure. Most expressed questions and anxiety about their health. Many found their communication with physicians about their DES exposure unsatisfying. They felt that physicians lacked information about the long-term health effects of DES exposure and as a result did not give them accurate information. Furthermore, they felt that physicians were dismissive of their concerns and often gave what they felt to be false reassurances. Consequently, the women developed an enduring distrust of the medical profession. The results of the study suggest implications for the delivery of health care to DES daughters. Copyright (C) 2000 John Wiley & Sons, Ltd.
8 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000089779700009, lens.org/076-727-546-105-731 tex.type: [object Object]
Keywords: *Abnormalities; Drug-Induced/px [Psychology]; *Carcinogens/ae [Adverse Effects]; *Diethylstilbestrol/ae [Adverse Effects]; *Focus Groups; *Genitalia; Female/de [Drug Effects]; *Nuclear Family/px [Psychology]; *Stress; Psychological/et [Etiology]; Abnormalities; Drug-Induced; Adult; Carcinogens; Diethylstilbestrol; Female; Focus Groups; Genitalia; Female; Human; Humans; Life Change Events; New York; Nuclear Family; Physician-Patient Relations; Self-Help Groups; Stress; Psychological; Support; U.S. Gov't; P.H.S.; adenocarcinoma; adult; anxiety; article; awareness; clinical article; clinical research; dept.hms; diethylstilbestrol; doctor patient relation; drug exposure; emotional stress; female; health care delivery; health education; health promotion; human; life event; patient counseling; patient education; patient satisfaction; physician attitude; prenatal care; risk assessment; social isolation; vagina cancer

Exposure to diethylstilbestrol: design of a multilevel community intervention - Duke, Suzanne S.; McGraw, Sarah A.; Avis, Nancy E. (Health Promotion Practice, 2000)
The planning of community health education interventions aimed at multiple levels is complex and challenging. This challenge is increased when a primary audience is difficult to reach. Individuals who were exposed to diethylstilbestrol (DES) decades ago represent a difficult-to-reach audience because they are not always aware of their exposure or the health risks of their exposure. However, DES-exposed individuals need specific screening and health care. An intervention was developed to increase awareness about DES in Nassau County, New York to address this concern. The Precede-Proceed Model was used to develop distinct intervention strategies to reach the general public, which includes individuals who may not be aware that they were exposed; those who are aware of their exposure but may not be following recommended health care practices; and community physicians. Behavioral targets, determining factors, and intervention goals were identified for each group. Specific intervention strategies were planned and implemented for each target audience. Addressing three target audiences simultaneously may produce a synergistic effect, enhancing program impact. © 2000, Sage Publications. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00199 tex.type: [object Object]
Keywords: dept.hms; peer-reviewed

Sensitivity to sensoriprocessing, self-discrepancy, and emotional reactivity of collegiate athletes. - Kemler, David S (Perceptual and Motor Skills, 2006)
This study investigated how differences between athletes who scored low and high on sensoriprocessing sensitivity apply self-discrepancies and emotional reactions to competitive sporting events. Two hypotheses were proposed: The High Sensitivity group (n = 33) would score higher for anxiety, guilt, and shame, and lower on pride and report more stress attributed to self-discrepancies than the Low Sensitivity group (n = 32) following competitive sports events. Collegiate varsity athletes were administered the High Sensitivity Scale prior to competition and completed the Selves Questionnaire and the Goal Congruent and Incongruent Emotion Scale immediately after competition. Scores for the High Sensitivity Scale were used to separate athletes into high and low sensitivity groups. A multivariate analysis of variance and subsequent univariate analyses indicated that the High Sensitivity group reported higher scores on anxiety, shame, and stress than the Low Sensitivity group. This was interpreted as reflecting differences between both ideal and ought self-discrepancies.
2 citations (Crossref) [2023-10-31] Place: United States Kemler, David S. Department of Exercise Science, Southern Connecticut State University, New Haven 06515, USA. kemlerd1@southernct.edu
Keywords: *Affect; *Cognition/ph [Physiology]; *Self Concept; *Sensation/ph [Physiology]; *Sports/px [Psychology]; *Universities; Adult; Affect; Awareness; Cognition; Female; Humans; Male; Psychological Theory; Questionnaires; Self Concept; Sensation; Sports; Surveys and Questionnaires; Universities; adult; affect; article; awareness; cognition; dept.hms; female; human; male; physiology; psychological aspect; psychological theory; questionnaire; self concept; sensation; sport; university